Improved reliability of wear performance for a fluorapatite veneering porcelain by ion-exchange strengthening and toughening. (December 2020) - Meng, M.; Li, X.C.; Li, D.; Guo, Z.X.; Li, K.Y.; Guo, J.W.; He, L.; Zhang, S.F.
Abstract: Objectives: Purpose of the present study was to explore the improvement of wear performance for a nano fluorapatite veneering porcelain by ion-exchange. Methods: Bar and disk specimens were prepared by IPS e.max Ceram as the nano fluorapatite veneering porcelain. Ion-exchange was performed in a melted KNO3 bath at two temperatures for different time-periods. After the ion-exchange, the bars were tested for flexural strength, surface Vickers hardness and HIF toughness, the disks were tested for wear performance paired with zirconia antagonist using a pin-on-disk tribometer with 10 N for 70✕10 4 wear cycles in artificial saliva. Wear analysis of the porcelain and zirconia was performed with a 3D profilometer. The microstructure and worn surface morphology were examined with scanning electron microscopy. One-way analysis of variance and Tukey's post-hoc pairwise comparison were used to analyse the wear data. Results: The nano fluorapatite veneering porcelain before ion-exchange presented strong time-dependent wear behavior. Furthermore, wear rate of the original porcelain exhibited a very large standard deviation in the running-in wear stage, which was correlated with highly inhomogeneous distribution of the characteristic fluorapatite crystals in the microstructure. After ion-exchange at 350 °C and 380 °C, especially after the processing at 350 °C for 128 h, the wear rates of both running-in and steady wear stages could be significantly decreased. More importantly, the standard deviation of wear rate in the running-in wear stage could be remarkably reduced after the treatment. The improved reliability of wear performance was attributed to the strengthening and toughening effects of the ion-exchange processing. Conclusion: For the fluorapatite veneering porcelain, the ion-exchange protocol to obtain an ion-exchange layer with less stress relaxation and a considerable depth could strengthen and toughen the porcelain; as a result, the reliability of wear performance could be remarkably improved.